Baudrillard Between Benjamin and McLuhan: ‘the Narcissistic Seduction’ of the Media Society - Lombardinilo, Andrea (Italian Sociological Review, 2017)
This paper aims to further investigate some aspects of Baudrillard’s analysis of the media society, influenced by Benjamin’s aesthetic teaching and McLuhan’s mediological legacy. His purpose is to probe the effects of the symbolic speedup fueled by the repeatability of messages and contents, constantly substituted by their immanent abstractions. The dominion of the signifier upon the signified, the replacement of the referendum with its referential highlights, the emphasis on the semiotic complexity of contemporary myths (as already remarked by Barthes), all this is destined to turn media into body extensions. Hence follows the ‘narcissistic seduction’ of television, as McLuhan outlines in reference to the tautological nature of mainstream media. In this sense, Baudrillard does not neglect the heuristic relevance of daily experience, conceived as an ‘open work’ by Eco. To the fore are the expressive shifts engendered by the cultural industry in the age of consumer fever. The result is Baudrillard’s syncretistic analysis of our communicative uncertainty. The latter stems from the meaningful and repeatable objects permeating the social act, increasingly influenced by the ‘narcissistic seduction’ of media.